Proporsi sifilis dini dan karakteristik wanita risiko tinggi di kabupaten Karo - Rini Chrisna; Kristina Nadeak; Richard Hutapea (Fakultas Kedokteran USU, 2013)
Introduction : Syphilis is chronic sexually transmited infection caused by Treponema pallidum (T. pallidum). The incidence of syphilis was high that its became important to prevent the spread. Karo Regency was selected as location of this study because it is a tourist area and having some locations of prostitution.To find proportion of early syphilis and characteristic of high risk women in Karo regencyMethods : This is a cross sectional descriptive study on 29 high risk women with early syphilis in Sempajaya, Kuta Bangun and Tiga Binanga, Karo Regency. Diagnosis of early syphilis established based on anamnesis, physical examination and serologic tests VDRL/TPHA.Result : Three cases of early latent syphilis were found in Karo Regency which two cases of early latent syphilis were found in Sempajaya and one case of early latent syphilis was found in Tiga Binanga. Most of the case was found at the age of 26- 35 years old group (34.5%). The majority of the ethnic is Karo (37.8%). The majority of patient’s education is elementary school (37.9%). Early syphilis mostly suffered by commercial sex worker (51.7%) and married (72.4%).Conclusion : Proportion of early syphilis in Karo Regency was 10.3%. Proportion of early syphilis in Sempajaya was 6.9%. Proportion of early syphilis in Tiga Binanga was 3.2%. Proportion of early latent syphilis was 100%. The high risk women mostly found in group of 26-35 years old, the ethnic is Karo, elementary school graduate, commercial sex worker and have been married.Key words : proportion; early syphilis; high risk women